2009
DOI: 10.1519/jsc.0b013e3181bb7388
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Time-of-Day-Specific Strength Training on Muscular Hypertrophy in Men

Abstract: The purpose of the present study was to examine effects of time-of-day-specific strength training on muscle hypertrophy and maximal strength in men. A training group underwent a 10-week preparatory training (wk 0-wk 10) scheduled between 17:00 and 19:00 hours. Thereafter, the subjects were randomized either to a morning or afternoon training group. They continued with a 10-week time-of-day-specific training (wk 11-wk 20) with training times between 07:00 and 09:00 hours and 17:00 and 19:00 hours in the morning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 20 publications
6
33
1
1
Order By: Relevance
“…To our best knowledge, the only study performed on humans found a tendency to smaller gains in muscle size when repeatedly training in the morning compared to the late afternoon hours (36). Although statistically insignificant, subjects training in the afternoon hours increased their m. quadriceps femoris volume, measured by magnetic resonance imaging, on average 30% more compared to their counterparts in the morning training group (36). One of the possible mechanisms contributing to the above-mentioned time-of-day-dependent training adaptations is signalling pathways involved in the control of protein synthesis and protein degradation.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…To our best knowledge, the only study performed on humans found a tendency to smaller gains in muscle size when repeatedly training in the morning compared to the late afternoon hours (36). Although statistically insignificant, subjects training in the afternoon hours increased their m. quadriceps femoris volume, measured by magnetic resonance imaging, on average 30% more compared to their counterparts in the morning training group (36). One of the possible mechanisms contributing to the above-mentioned time-of-day-dependent training adaptations is signalling pathways involved in the control of protein synthesis and protein degradation.…”
Section: Introductionmentioning
confidence: 86%
“…Furthermore, early morning and late afternoon hours are also when hormonal signalling is dramatically different (e.g., cortisol to testosterone ratio -for a review see (16)). Considering the limited results from the acute studies (4) and from the long-term studies (36), it can be hypothesized that the time of day might influence the response to an acute bout of resistance exercise at the molecular level, e.g. hypertrophic signalling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…83 Sedliak et al measured muscle volume to determine the effects of training-induced muscle hypertrophy at a specific time of day for 10 weeks in men. 84 The results showed that 10 weeks of training in the morning or in the evening increased the cross-sectional area of the quadriceps femoris muscle by 2.7% and 3.5%, respectively, but the difference was not significant. 84 Adaptation to training is temporally specific to increase muscle strength, but not muscle volume, in adult humans.…”
Section: Nakao Et Al Chronoexercisementioning
confidence: 91%
“…84 The results showed that 10 weeks of training in the morning or in the evening increased the cross-sectional area of the quadriceps femoris muscle by 2.7% and 3.5%, respectively, but the difference was not significant. 84 Adaptation to training is temporally specific to increase muscle strength, but not muscle volume, in adult humans. 83,84 Whether or not a specific time of training would improve sarcopenia in aged populations should be determined.…”
Section: Nakao Et Al Chronoexercisementioning
confidence: 91%
See 1 more Smart Citation